2009
DOI: 10.1177/1049732309333242
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Involuntarily Childless Turkish Immigrants in the Netherlands

Abstract: The consequences of involuntary childlessness are influenced by culture in several ways. In this study we explored the experiences and responses of infertile Turkish immigrants in the Netherlands. Twenty in-depth interviews were conducted with involuntarily childless Turkish immigrants in the Netherlands (11 couples and 9 women). Interviews were transcribed verbatim and were analyzed using interpretative phenomenological analysis (IPA). The respondents' experiences were clustered around six superordinate theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
1
10
0
11
Order By: Relevance
“…In the current study lack of relationship intimacy was reported as one of the effects of infertility related to concentrating on having sexual relation to become pregnant. Consistently, in a study of Turkish women, the respondents reported negative influence of fertility problems on the sexual relationships within couples as change in the patterns of their relationships, tension and arguments between partners [36].…”
Section: Discussionmentioning
confidence: 61%
“…In the current study lack of relationship intimacy was reported as one of the effects of infertility related to concentrating on having sexual relation to become pregnant. Consistently, in a study of Turkish women, the respondents reported negative influence of fertility problems on the sexual relationships within couples as change in the patterns of their relationships, tension and arguments between partners [36].…”
Section: Discussionmentioning
confidence: 61%
“…Infertility for British Pakistanis is therefore seen to constitute a problem not just for the individual (or couple), but one that involves extended families and wider communities (see also Schmid et al, 2004;Van Rooij et al, 2006;and Van Rooij and Van Balen, 2009, for similar findings among other minority Muslim populations in Europe). In this paper, we take the idea of relationality a stage further, by exploring the role of extended families in defining and shaping the experience of infertility in the context of changing family aesthetics.…”
mentioning
confidence: 85%
“…Although fertility research is frequently based on interviews with female patients as well as couples, the fact that couples were interviewed together can be viewed as a limitation of the study (van Rooij et al, 2009;Wilkes et al, 2009). It is possible that if both partners were interviewed separately their views would differ.…”
Section: Discussionmentioning
confidence: 99%
“…Both female patients and couples were selected. In interview studies with infertility patients, couples and female patients are often both included (de Lacey, 2007;van Rooij et al, 2009;Wilkes et al, 2009).…”
Section: Methodsmentioning
confidence: 99%